2011
DOI: 10.1186/1471-2164-12-493
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic analyses of Mycobacterium bovis BCG Mexico 1931 reveal a diverse immunogenic repertoire against tuberculosis infection

Abstract: BackgroundStudies of Mycobacterium bovis BCG strains used in different countries and vaccination programs show clear variations in the genomes and immune protective properties of BCG strains. The aim of this study was to characterise the genomic and immune proteomic profile of the BCG 1931 strain used in Mexico.ResultsBCG Mexico 1931 has a circular chromosome of 4,350,386 bp with a G+C content and numbers of genes and pseudogenes similar to those of BCG Tokyo and BCG Pasteur. BCG Mexico 1931 lacks Region of Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…In this study, we also identified 25 RDs (11 previously published [3], [18], [22], [25], [26], [27], [28] and 14 new; Table S4) that cover one or more absence genes in the genome sequences of these BCG strains. The topological structure tree based on RDs (Figure 2b) more clearly shows the relationship among the M. bovis BCG and M. tuberculosis strains than does the NJ phylogenetic tree (Figure 2a).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, we also identified 25 RDs (11 previously published [3], [18], [22], [25], [26], [27], [28] and 14 new; Table S4) that cover one or more absence genes in the genome sequences of these BCG strains. The topological structure tree based on RDs (Figure 2b) more clearly shows the relationship among the M. bovis BCG and M. tuberculosis strains than does the NJ phylogenetic tree (Figure 2a).…”
Section: Resultsmentioning
confidence: 95%
“…Whole genome sequences of M. bovis (AF2122/97), seven strains of M. bovis BCG (BCG Mexico, BCG China, BCG Russia, BCG Tice, BCG Danish, Tokyo 172 and Pasteur) and five strains of M. tuberculosis (H37Rv, H37Ra, F11, KZN1435 and CDC1551) were downloaded from the NCBI database [3], [10], [11], [12], [13], [14], [15], [16], [17], [18]. Detailed information about these strains is listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, sequencing of BCG Mexico 1931 repositioned this strain from the DU2-III group into the DU2-IV group that includes BCG Pasteur, BCG Connaught, BCG Tice, BCG Frappier, and BCG Phipps. This analysis revealed that BCG Mexico was not originally derived from BCG Danish, as previously thought, and that this inconsistency was likely attributed to different BCG manufacturing periods in Mexico (69). Additionally, this project uncovered novel deletions in BCG Mexico that shed light on its evolution.…”
Section: Molecular Evolution and The Propagation Of Bcg Substrainsmentioning
confidence: 52%
“…The sequences of these strains such as Tokyo 172 (NC_012207.1) and Moreau RDJ (NZ_AM412059.1) were generated from the small-insert libraries (1-4 kb) by using BigDye terminator chemistry on ABI377-or ABI3700-automated DNA sequencers [9][10][11][12]. The large-insert library (40 bp) preparation method was used for Mexico BCG sub-strain (NC_016804.1) sequencing [13]. Orduña et al [13] were first who used for BCG genome analysis -the next generation sequencing (NGS) based on 454 technology and Sanger method.…”
Section: Bcg Genome Sequencingmentioning
confidence: 99%